1997
DOI: 10.1007/s004390050437
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen metabolism for the pathological phenotype of Fanconi anemia

Abstract: The molecular defect of the hereditary disease Fanconi anemia (FA) remains unknown. The two theoretical possibilities are (1) an impaired DNA crosslink-repair system or (2) a disturbed oxygen metabolism either by overproduction of reactive oxygen intermediates (ROI) or by diminished detoxification of ROI. In order to gain further insight into the molecular mechanism of this disease, we have determined the repair capacity of FA cells challenged by crosslinking agents and have analyzed diverse biological systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 65 publications
(66 reference statements)
1
46
0
1
Order By: Relevance
“…[12][13][14] CY is a prodrug which requires metabolic transformation to generate active alkylating species. The initial activation is thought to be mediated by a hepatic cytochrome P450 reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] CY is a prodrug which requires metabolic transformation to generate active alkylating species. The initial activation is thought to be mediated by a hepatic cytochrome P450 reaction.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9] The increased sensitivity of FA patients to CY has been ascribed either to deficiencies in DNA repair 10,11 or to disturbed oxygen metabolism with overproduction of reactive oxygen intermediates. [12][13][14] CY is a prodrug which requires metabolic transformation to generate active alkylating species. The initial activation is thought to be mediated by a hepatic cytochrome P450 reaction.…”
mentioning
confidence: 99%
“…21,22 A potential endogenous source of superoxide, the NADPH cytochrome P-450 reductase (RED) system, has also been implicated in FA. Not only were chromosomal breaks in FA cells reduced by cytochrome P-450 inhibition, but evidence of a direct physical interaction between FANCC and RED was reported, 23,24 leading to the hypothesis that FANCC might protect cells from ROS via regulation of RED activity.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 A potential endogenous source of superoxide, the NADPH cytochrome P-450 reductase (RED) system, has also been implicated in FA. Not only were chromosomal breaks in FA cells reduced by cytochrome P-450 inhibition, but evidence of a direct physical interaction between FANCC and RED was reported, 23,24 leading to the hypothesis that FANCC might protect cells from ROS via regulation of RED activity.Mice with a targeted disruption of the gene encoding the cytosolic Cu/Zn SOD (Sod1) exhibit normal growth and development; however, they show a distinctive motor axonopathy 25,26 and impaired gametogenesis. 27 The limited spontaneous pathology of Sod1 Ϫ/Ϫ mice suggested that although this enzyme might function to modulate superoxide-mediated effects in some tissues under basal conditions, that it was of critical importance during exposures to specific pro-oxidant stimuli.…”
mentioning
confidence: 99%
“…Antioxidants exert a stabilizing in¯uence on FA DNA and FA cells (Dallapiccola et al, 1985;Ruppitsch et al, 1997). Interestingly, the amount of antioxidative enzymes like catalase, superoxide dismutase, glutathione peroxidase, and phospholipid hydroperoxide glutathione peroxidase are normal in FA ®broblasts (Gille et al, 1987;Ruppitsch et al, 1997). Nevertheless, the intracellular content of reactive oxygen intermediates is elevated (Korkina et al, 1992).…”
Section: Introductionmentioning
confidence: 99%